Bio-Psycho-Spiritual Modeling in Drug Dependents and Compiling of Intervention Program for Promotion of Resiliency Based on Cognitive Narratology and Positive Psychology - Ezat ollah Kordmirza Nikoozadeh; Ahmad Borjali; Hosin Eskandari; Faramarz Sohrabi; Ali Delavar (Drug Control Headquarters, Research and Education Office, 2009)
Introduction: Since the past few decades, the concentration of researches on drug abuse and drugs dependency have shift from risk factor to protective factors. In the past two decades, the concept of resiliency was increasingly considered by developmental psychology. The concentration shifted from risk to resiliency originates from disadvantage in emphasizing on identification of risk factors. Method: Target population was all volunteer addicts who referred to clinics in Tehran city. The group selected based on random cluster sampling. In total 319 persons (male) composed of two groups, dependent to drug (150 persons) and independent to drug (169 persons) were participated in research and in general, 108 questionnaires of non-addicts and 126 of addicts were analyzed. In order to determine the fit model based on assumed variables in the research, by utilizing LISREL softwar99e, initially the relation between primary fundamental variables and final endogenous variables were reviewed. In continuation, the - relations between intermediary and endogenous variables were determined. Results: The results showed the fitting of predicted model of resiliency. Conclusion: In this research the program based on bio-psycho-spiritual model for instructional intervention in order to enhance of resiliency of addict people provided.